Implementasi Smart Health Platform di Wuhan, Hubei: Infrastruktur, Standarisasi Data, dan Tantangan Teknis - Nisaa, Arifatun; Juansheng, Wen; Juncheng, Cai (Politeknik Negeri Jember, 2025)
The advancement of information technology has accelerated the transformation of healthcare services through the Smart Health Platform (SHP), designed to improve quality, efficiency, and system integration. In Wuhan, Hubei, SHP implementation faces challenges that must be addressed to achieve digital health objectives. Key issues involve infrastructure, data standardization, and technical factors. Infrastructure limitations such as network capacity, server capability, and inter-facility integration remain barriers. Data standardization is hindered by variations in formats and inconsistencies across hospitals, complicating information exchange. Technical challenges include data security, system interoperability, and human resource readiness. This study analyzes the influence of these factors on SHP effectiveness using a quantitative descriptive method. A Likert-scale questionnaire was distributed to 424 active users, and data were analyzed with descriptive statistics and multiple linear regression. Results show that all three variables significantly affect SHP effectiveness (R² = 0.507; p < 0.05). Infrastructure and data standardization contribute positively, while technical challenges exert a negative effect. The study concludes that strengthening infrastructure, harmonizing data, and enhancing human resource capacity are critical to ensuring the success of integrated digital healthcare systems.